PENGARUH PENGGUNAAN MEDIA INTERAKTIF QUIZIZZ PAPER MODE TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IIIB SDK MARIA FERARRI - Kumbartama, Yoaklina Devedruna Kumbartama; Sonya Maria Kristiani; Maria Herliyani Dua Bunga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of using interactive media Quizizz Paper Mode on the mathematics learning outcomes of grade IIIB students at SDK Maria Ferarri. Based on initial observations, mathematics learning was still dominated by conventional methods, resulting in less optimal student learning outcomes, particularly on the topic of multiplication as repeated addition. This study employed a quantitative research method with the population consisting of all 37 students of class IIIB at SDK Maria Ferarri. A saturated sampling technique was used, in which all members of the population were taken as the research sample. Data were collected through learning outcome tests and documentation, with test questions serving as the research instrument. The results of the study indicate that there is a significant effect of using interactive media Quizizz Paper Mode on students’ mathematics learning outcomes. This is evidenced by an increase in the average student score from a pretest score of 65.42 to a posttest score of 94.05. Based on the results of hypothesis testing at a significance level of 0.05, a significance value of 0.000 < 0.05 was obtained, indicating that H₀ was rejected and Hₐ was accepted. Therefore, it can be concluded that the use of interactive media Quizizz Paper Mode is effective in improving students’ mathematics learning outcomes on the topic of multiplication as repeated addition in class IIIB at SDK Maria Ferarri.